Optimal time of the attacking action in kendo - James Ogle; Peter O'Donoghue (Asociación Española de Ciencias del Deporte, 2015)
The aim of this study was to investigate whether the time of an attacking action influenced the success rate of ippon (valid point) in international, elite level kendo. Selected videos of elite kendo competitors were viewed using Kinovea where the time of the attacking action could be analysed frame by frame. Movements were measured from the start of the forward or downward movement of the shinai until impact or until the point of the shinai had passed through the target area if the cut was a complete miss. There were 7.6% of attacks of 0.09s-0.12s and 6.5% of attacks of 0.13s-0.15s that led to ippon. This was a greater success rate than shorter or longer attacks. The timings of attacks performed by competitors who reached the quarter finals of tournaments were significantly faster (p < 0.001) and significantly more consistent (p = 0.006) than those performed by competitors eliminated prior to the quarter finals. These results suggest there is an optimal timing range in kendo that produces a winning strike. Mechanisms are needed to evaluate performance indicators where there are optimal values maximise the chance of success.